2012
DOI: 10.1007/s00402-012-1651-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of spinal cord injury without radiologic evidence of trauma with cervical disc herniation

Abstract: CDH in most patients with SCIWORET likely occurred before rather than after trauma. CDH caused more severe cord compression but did not aggravate the neurologic injury. The extent of MSCC had no association with the initial neurologic deficit or final recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The rate of disc injury ranged from 4% to 42% in studies involving cervical SCIWORA, whereas it was 40% to 88% in other SCI studies [ 20 , 21 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 37 , 41 , 42 , 43 , 44 ]. Disc herniation was present in 37% to 100% of patients with SCIWORA, whereas it was present in 24% to 100% in SCI [ 20 , 21 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 37 , 41 , 42 , 43 , 44 ]. Disc herniation causing cord compression varied from 3% to 83% in two studies involving SCI [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The rate of disc injury ranged from 4% to 42% in studies involving cervical SCIWORA, whereas it was 40% to 88% in other SCI studies [ 20 , 21 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 37 , 41 , 42 , 43 , 44 ]. Disc herniation was present in 37% to 100% of patients with SCIWORA, whereas it was present in 24% to 100% in SCI [ 20 , 21 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 37 , 41 , 42 , 43 , 44 ]. Disc herniation causing cord compression varied from 3% to 83% in two studies involving SCI [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 96%
“…Overall, 28 studies relevant to KQ2 were identified, reporting the frequency of certain pathological MRI findings in various types of SCI ( Table 4 ) [ 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations